2003
DOI: 10.1016/j.bbrc.2003.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking and surface expression of the glutamate receptor subunit, KA2

Abstract: Kainate receptors are a class of ionotropic glutamate receptors that are widely expressed in the mammalian brain, yet little is known about their physiological role or the mechanisms by which they are regulated. Kainate receptors are composed of multiple subunits (GluR5-7; KA1-2), which can combine to form homomeric or heteromeric channels. While the kainate receptor subunit KA2 can combine with GluR5-7 to form heteromeric channels, it does not form functional homomeric channels when expressed alone. In an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
(45 reference statements)
2
33
0
Order By: Relevance
“…Electrophysiology Methods-HEK-293 cells were transiently transfected with NR1-1a and FLAG-NR2C-IRES-EGFP as described previously (17). Between 2 and 3 days after transfection, cells were used for electrophysiology with transfected cells identified by visualizing GFP fluorescence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiology Methods-HEK-293 cells were transiently transfected with NR1-1a and FLAG-NR2C-IRES-EGFP as described previously (17). Between 2 and 3 days after transfection, cells were used for electrophysiology with transfected cells identified by visualizing GFP fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence-activated Cell Sorting (FACS) Analysis-HEK-293 cells were transiently transfected with NR1-1a and FLAG-NR2C-IRES-EGFP as described previously (17). Transfected HEK-293 cells were rinsed twice with PBS containing 5 mM EDTA (PBS/EDTA) and then incubated with PBS/EDTA for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike GluR6, KA2 does not exist as functional homomers, and it is likely that neurons use precise quality control mechanisms to regulate the oligomerization and trafficking of KA2. Recently, it was demonstrated that KA2 is endoplasmic reticulum (ER) retained when expressed in heterologous cells (Gallyas et al, 2003;Hayes et al, 2003;Ren et al, 2003). The molecular mechanisms regulating KA2 ER-retention likely play a critical role in regulating the complement of synaptic kainate receptors, because they ensure that KA2 only reaches the plasma membrane as a heteromeric channel.…”
Section: Introductionmentioning
confidence: 99%
“…76 GluK5 subunits can form homomeric receptors, but these are not surface expressed because they are retained in the ER. [77][78][79] These subunits contain an RXR motif in the intracellular region between the second and third membrane domains 80 and an intracellular C-terminal arginine-rich (RRRRR) ER retention/retrieval motif. This motif is a binding site for the coatomer protein I (COPI) 81 a component of the retrograde trafficking protein complex that mediates the transport of defective proteins back from the Golgi to the ER.…”
Section: Molecular Determinants Of Kar Traffic Er Retention/retrievalmentioning
confidence: 99%